Digestibility and Nutritional Value of Fermented Straw Supplemented with Green Concentrate as Feed Ingredients for Holstein Friesian Dairy Cattle - Abdul Hakim Fattah; K. Khaeruddin (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
The purpose of this study was to determine the effect of fermented straw supplementation with green concentrate on nutrient content and nutrient digestibility. Green concentrate used as treatment was white lead tree leaf flour (Leucaena leucocephala), Gamal leaf meal (Gliricidia sepium), and Indigofera leaf meal. Proximate analysis was carried out on fermented rice straw, 70% fermented rice straw + 30% lamtoro (FRS + white lead tree), 70% fermented rice straw + 30% Gamal (FRS + Gamal) and 70% fermented rice straw + 30% Indigofera (FRS + Indigofera). The livestock used for the nutrient digestibility test was 12 Friesian Holstein dairy cows. A randomized block design was used to test nutrient digestibility. The results showed that supplementation of green concentrate in fermented rice straw was able to increase crude protein, crude fat, and BETN and decrease crude fiber. Crude protein digestibility did not differ in the three types of green concentrates. Crude fat digestibility of FRS + white lead tree and FRS + Indigofera was higher than FRS + Gamal. The digestibility of BETN FRS + Gamal was higher than the digestibility of FRS + white lead tree and FRS + Indigofera. This study concludes that the three types of green concentrate can be used for the supplementation of fermented rice straw as dairy cattle feed.